"I just want you to hear that term": Characterizing language used in fetal cardiology consultations: Presenter(s): Kelly Harris, University of Pittsburgh School of Medicine, United States; Kelsey Schweiberger, University of Pittsburgh School of Medicine, United States. (April 2023) - Kavanaugh-McHugh, Ann; Arnold, Robert; Merlin, Jessica; Kasparian, Nadine; Chang, Judy
Abstract : Background: Communication with parents during pregnancy about complex congenital heart disease (CHD) can significantly influence parental understanding of, and psychological responses to, the diagnosis. Fetal cardiac consultations provide an important opportunity to optimize this communication. Prior research suggests words clinicians use to describe CHD, such as "heart difference" rather than "heart defect", may be important to parents. However, little is known about the language used in fetal cardiac consultations. Methods: Initial fetal cardiology consultations with parents for potentially complex CHD were audio-recorded, transcribed verbatim, and coded by two independent coders. A codebook was inductively developed and applied to all transcripts. Coding differences were adjudicated to full agreement. The final coding framework was used to identify communication patterns and themes. Findings: In the 19 audio-recorded consultations across five fetal cardiology clinicians at one academic institution, 14 different cardiac diagnoses were discussed (seven with low and seven with high risk of mortality). We identified three themes for language used to describe CHD: medical, plain, and patient-centered language. Each consultation utilized all three types of language with plain language used most frequently. Plain language often was used to define and emphasize the meaning behind medical language. While less frequently used, patient-centered language emphasized the child as a whole person with value and worth beyond their heart condition. Discussion: Fetal cardiology clinicians in our study used plain language to define and describe medical language for parents. They employed patient-centered language to center counseling on the child rather than the pathology. Similar clinician language may help familiarize and empower parents with the tools to understand their child's condition and communicate with their medical team. Future research should focus on clinicians' communication intentions and the consequences of their language use on parents' decision-making, psychological adjustment, mental health, and quality of life outcomes.